Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 10 - Radical Expressions and Equations - 10-2 Simplifying Radicals - Practice and Problem-Solving Exercises: 70

Answer

$x= -3 ± 3\sqrt 2$

Work Step by Step

The trinomial cannot be factored so we use the quadratic formula to calculate the x. $x= \frac{-b ± \sqrt (b^{2} - 4ac)}{2a}$ $x^{2} + 6x -9$ In this trinomial a = 1, b= 6 and c= -9 $x= \frac{-(6) ± \sqrt (6^{2} - 4(1)(-9))}{2(1)}$ $x= \frac{-6 ± \sqrt (36 + 36)}{2}$ $x= \frac{-6 ± \sqrt (72)}{2}$ Square root of 72 is $6\sqrt 2$ because the factors of 72 are 36 and 2 and 36 is a perfect square of 6. $x= \frac{-6 ± 6\sqrt 2}{2}$ We simplify the numbers to get the final x value. $x= -3 ± 3\sqrt 2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.